2014
DOI: 10.1186/1743-7075-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Miglitol increases energy expenditure by upregulating uncoupling protein 1 of brown adipose tissue and reduces obesity in dietary-induced obese mice

Abstract: BackgroundMiglitol is an oral anti-diabetic drug that acts by inhibiting carbohydrate absorption in the small intestine. Recent studies have shown that miglitol reduces obesity in humans and rodents. However, its mechanisms have remained unclear. The purpose of this study was to determine whether miglitol generates heat by activating uncoupling protein 1 (UCP1), an enzyme involved in thermogenesis, in brown adipose tissue (BAT) in mice.MethodsFour-week-old male C57BL/6 J mice were fed a high-fat diet alone (HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 33 publications
4
29
1
1
Order By: Relevance
“…Uncoupling protein 1 ( UCP-1 ), a brown fat-specific gene, is an energy metabolism-related factor that plays a central regulator role in mitochondrial biogenesis and thermogenesis in BAT [23]. In our study, we observed significantly decreased (−59%, p = 0.005) mRNA levels of UCP-1 in obese rats when calculated with the combination of most stable reference genes ( 36B4 and β-actin ).…”
Section: Resultsmentioning
confidence: 46%
“…Uncoupling protein 1 ( UCP-1 ), a brown fat-specific gene, is an energy metabolism-related factor that plays a central regulator role in mitochondrial biogenesis and thermogenesis in BAT [23]. In our study, we observed significantly decreased (−59%, p = 0.005) mRNA levels of UCP-1 in obese rats when calculated with the combination of most stable reference genes ( 36B4 and β-actin ).…”
Section: Resultsmentioning
confidence: 46%
“…NE, via b 3 -adrenoceptor, initiates triacylglycerol breakdown through BAT thermogenesis. The intracellular signal is transmitted via cAMP and protein kinase A, leading to the release from triacylglycerols of fatty acids that are both the acute substrate for thermogenesis and the regulators of the activity of UCP1 [33]. It is noteworthy that continuous stimulation of NE leads to the dramatic downregulation of b3 expression levels [1].…”
Section: Discussionmentioning
confidence: 98%
“…The route and timing of excretion of α-GIs in patients who have undergone gastric resection may affect the efficacy against hypoglycemia. Recently, it has been shown that miglitol enhanced β3-adrenergic signaling in brown adipose tissue [33,34]. These reports raised the possibility that miglitol can modulate the activity of sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 97%